2021
DOI: 10.33860/jik.v15i1.430
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kesediaan Masyarakat menerima Vaksinasi Covid-19 di Sulawesi Tengah

Abstract: Tujuan penelitian untuk mengetahui determinan kesediaan masyarakat menerima vaksinasi Covid-19 di Sulawesi Tengah. Penelitian deskriptif analitik desain cross sectional pada Januari tahun 2021. Survei online masyarakat di Sulawesi Tengah dengan 266 orang responden berusia 18 tahun ke atas. Pengumpulan data secara accidental sampling melalui https://ee.kobotoolbox.org/x/aSWgcPdw dan dianalisis menggunakan SPSS 22,0 uji chi square dan regresi logistik kemaknaan p-value 0,05%. Hasil penelitian menunjukkan respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
32

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 4 publications
3
10
0
32
Order By: Relevance
“…Because young individuals are also at risk for COVID-19 infection, the findings of the Ichsan research, et al (2021) revealed to the general public that young people who refuse to get vaccinated are targeted for socialization and education. To decrease the total occurrence, appropriate messaging based on age and other aspects to enhance mitigation adherence among the less susceptible, more mobile, and lower priority vaccination age categories will be a necessity and continuous priority (Ichsan et al, 2021). Expectant mother's knowledge is impacted by their degree of education, and the findings of this present study support previous findings that pregnant women's awareness in their effort to protect themselves from COVID-19 is influenced by their level of education (Besho et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Because young individuals are also at risk for COVID-19 infection, the findings of the Ichsan research, et al (2021) revealed to the general public that young people who refuse to get vaccinated are targeted for socialization and education. To decrease the total occurrence, appropriate messaging based on age and other aspects to enhance mitigation adherence among the less susceptible, more mobile, and lower priority vaccination age categories will be a necessity and continuous priority (Ichsan et al, 2021). Expectant mother's knowledge is impacted by their degree of education, and the findings of this present study support previous findings that pregnant women's awareness in their effort to protect themselves from COVID-19 is influenced by their level of education (Besho et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Hubungan antara usia dengan penerimaan masyarakat terhadap vaksinasi Covid-19 mendapatkan hasil uji statistik nilai p value = 0,096 yang bermakna tidak ada hubungan. Hasil penelitian ini tidak sejalan dengan penelitian yang dilakukan oleh Ichsan et al, (2021) dan Alshurman et al, (2021) menemukan bahwa terdapat hubungan antara usia dengan penerimaan dalam melakukan vaksinasi Covid-19. Namun, penelitian lain yang sejalan dengan penelitian ini yang dilakukan oleh Utama et al, (2021) yang menemukan bahwa tidak adanya hubungan usia dengan penerimaan vaksinasi Covid-19.…”
Section: Diskusiunclassified
“…Hal ini didukung oleh Irwan (2017) dimana proses pengambilan keputusan sangat didasarkan oleh kemampuan kognitif yang baik yang dapat diperoleh dengan mencapai tingkat pendidikan yang tinggi. Namun hasil penelitian ini bertentangan dengan penelitian yang dilakukan oleh Ichsan et al, (2021) yang menemukan hasil bahwa terdapat hubungan antara tingkat pendidikan dengan sikap penerimaan masyarakat terhadap vaksinasi Covid-19.…”
Section: Diskusiunclassified
“…Age is related to the decision to receive the COVID-19 vaccination. Older ages, such as those at retirement age, tend to be more prepared to receive COVID-19 vaccinations (Akiful Haque et al, 2021;Ichsan et al, 2021). People who are younger than 30 years tend to refuse COVID-19 vaccination (Walsh et al, 2022).…”
Section: Agementioning
confidence: 99%